Faktor-Faktor Yang Mempengaruhi Penerimaan Sistem Informasi Menggunakan Model TAM - Cut Asiana Gemawaty; Yuce Yuliani (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
This study aims to analyze the factors that influence the acceptance of an information system using the Technology Acceptance Model (TAM). The research examines three key constructs: Perceived Usefulness (PU), Perceived Ease of Use (PEOU), and Behavioral Intention (BI). A quantitative approach was employed with a purposive sampling technique involving 60 active users of the information system. Data were collected using a Likert-scale questionnaire and analyzed using SPSS through validity testing, reliability testing, descriptive statistics, and Spearman correlation analysis. The findings indicate that all measurement instruments demonstrate excellent validity and reliability, with Cronbach’s Alpha values exceeding 0.900 for all variables. The correlation results reveal that both PU and PEOU have positive and significant relationships with BI, suggesting that perceived benefits and ease of use are important determinants that strengthen users’ intention to adopt and continue using the system. However, the relationship between PEOU and PU is not significant, indicating that ease of use does not automatically translate into perceived usefulness within the context of this study. These results reinforce the relevance of the TAM framework while highlighting contextual nuances that may influence variable relationships. Overall, the study concludes that enhancing system usefulness and ensuring ease of use are essential strategies for increasing user acceptance of information systems within organizational settings.